2014
DOI: 10.1021/la404144a
|View full text |Cite
|
Sign up to set email alerts
|

Shape Transitions in Supercritical CO2 Microemulsions Induced by Hydrotropes

Abstract: The ability to induce morphological transitions in water-in-oil (w/o) and water-in-CO2 (w/c) microemulsions stabilized by a tri-chain anionic surfactant 1,4-bis(neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-sulfonate (TC14) with simple hydrotrope additives has been investigated. High pressure small-angle neutron scattering (SANS) has revealed the addition of a small mole fraction of hydrotrope can yield a significant elongation in the microemulsion water droplets. For w/o systems, the degree of drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…The effect of pressure on SANS was also examined for a pure D2O core system and similar results were obtained as for the H2O/D2O mixed core systems. Furthermore, although formation of elongated w/c microemulsions has been reported in a few studies [14][15][16] , this is the first observation of anisotropic micellar structures triggered by changing CO2 pressure and bulk density. In Table 3, the fitting parameters obtained using the cylindrical form factor model have been compared for w/c systems stabilized by 4FS(EO)2 and 6FS(EO)2, together with other systems containing cylindrical micelles reported in the literature 11,15 .…”
Section: Effect Of Co2 Bulk Densitymentioning
confidence: 60%
See 2 more Smart Citations
“…The effect of pressure on SANS was also examined for a pure D2O core system and similar results were obtained as for the H2O/D2O mixed core systems. Furthermore, although formation of elongated w/c microemulsions has been reported in a few studies [14][15][16] , this is the first observation of anisotropic micellar structures triggered by changing CO2 pressure and bulk density. In Table 3, the fitting parameters obtained using the cylindrical form factor model have been compared for w/c systems stabilized by 4FS(EO)2 and 6FS(EO)2, together with other systems containing cylindrical micelles reported in the literature 11,15 .…”
Section: Effect Of Co2 Bulk Densitymentioning
confidence: 60%
“…Although these cylindrical structures are not sufficiently anisotropic to drive significant viscosity enhancements, this is a very interesting observation which deserves further attention. Instead of changing the chemical compositions in the surfactant film by using designed surface-active additives 18 , hydrotropes 16 or chemical methods such as ion exchange in the headgroups 17 , the bulk density of scCO2 could represent a…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 And even for those specifically designed surfactants that effectively stabilise 13 water-in-CO2 (w/c) microemulsions, modification of the self-assembled structures, which 14 has been well-established as an effective method to enhance the viscosity in alkane solvent, 15 is generally inhibited in scCO2. 16 In one of the very few reports on anisotropic self-assembled structures in scCO2, it was 17 found that by exchanging the surfactant counter ion Na + with divalent species such as Co 2+ 18 and Ni 2+ , a sphere-rod shape transition can be obtained for the micelles formed not only in 19 alkane solvents with hydrocarbon surfactants, 12 but also in scCO2. 4 However, the shape 20 transitions were only observed at very low water content with water: surfactant molar ratio 21 (W = [water]/[surf]) ≤ 10, and furthermore, micelles formulated by the counter-ion 22 exchanged surfactants generally require a relatively high pressures (~300 bar) to be 23 stabilised in scCO2.…”
mentioning
confidence: 99%
“…15,16 Interesting shape transitions between 8 spherical-cylindrical structures have been reported for a number of AOT stabilised water-in- 9 oil (w/o) microemulsions on addition of certain hydrotropes. In recent work, 17 effects of 10 such hydrotrope additives have been investigated with a custom-made tri-chain 11 hydrocarbon CO2-active surfactant (TC14), and using High-Pressure Small-angle neutron 12 scattering (HP-SANS) elliptical micelles were confirmed for microemulsions in both alkane 13 solvents and scCO2. That initial study is significant in the development of viscosity modifiers 14 for applications in scCO2, not only because it represents a new approach to promote 15 micellar growth, but also because the same general effects of hydrotropes are found in both 16 water-in-oil (w/o) and water-in-CO2 (w/c) microemulsions.…”
mentioning
confidence: 99%